Integrating ensemble machine learning and multi-omics approaches to identify Dp44mT as a novel anti-Candida albicans agent targeting cellular iron homeostasis - Chai, Xiaowei; Jiang, Yuanying; Lu, Hui; Huang, Xin (Frontiers in Pharmacology, 2025)
IntroductionCandidiasis, mainly caused by Candida albicans, poses a serious threat to human health. The escalating drug resistance in C. albicans and the limited antifungal options highlight the critical need for novel therapeutic strategies.MethodsWe evaluated 12 machine learning models on a self-constructed dataset with known anti-C. albicans activity. Based on their performance, the optimal model was selected to screen our separate in-house compound library with unknown anti-C. albicans activity for potential antifungal agents. The anti-C. albicans activity of the selected compounds was confirmed through in vitro drug susceptibility assays, hyphal growth assays, and biofilm formation assays. Through transcriptomics, proteomics, iron rescue experiments, CTC staining, JC-1 staining, DAPI staining, molecular docking, and molecular dynamics simulations, we elucidated the mechanism underlying the anti-C. albicans activity of the compound.ResultAmong the evaluated machine learning models, the best predictive model was an ensemble learning model constructed from Random Forests and Categorical Boosting using soft voting. It predicts that Dp44mT exhibits potent anti-C. albicans activity. The in vitro tests further verified this finding that Dp44mT can inhibit planktonic growth, hyphal formation, and biofilm formation of C. albicans. Mechanistically, Dp44mT exerts antifungal activity by disrupting cellular iron homeostasis, leading to a collapse of mitochondrial membrane potential and ultimately causing apoptosis.ConclusionThis study presents a practical approach for predicting the antifungal activity of com-pounds using machine learning models and provides new insights into the development of antifungal compounds by disrupting iron homeostasis in C. albicans.